2014
DOI: 10.1021/jf502259j
|View full text |Cite
|
Sign up to set email alerts
|

Tracking (Poly)phenol Components from Raspberries in Ileal Fluid

Abstract: The (poly)phenols in ileal fluid after ingestion of raspberries were analyzed by targeted and nontargeted LC-MS(n) approaches. Targeted approaches identified major anthocyanin and ellagitannin components at varying recoveries and with considerable interindividual variation. Nontargeted LC-MS(n) analysis using an orbitrap mass spectrometer gave exact mass MS data which were sifted using a software program to select peaks that changed significantly after supplementation. This method confirmed the recovery of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 36 publications
0
62
0
Order By: Relevance
“…The crude extracts were used to determine the total phenolic and flavonoid contents. The purified extracts were lyophilized and used for antioxidant, antimicrobial and antiproliferative activity determinations as well as UPLC/ESI‐QTOF‐MS analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The crude extracts were used to determine the total phenolic and flavonoid contents. The purified extracts were lyophilized and used for antioxidant, antimicrobial and antiproliferative activity determinations as well as UPLC/ESI‐QTOF‐MS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The optimal values of the source parameters were as follows: capillary voltage, 4 kV; drying gas flow, 10 L min −1 ; drying gas temperature, 350 °C; nebulizing gas pressure, 40 psi. Moreover, the pseudo‐molecular ions [M − H] − were selected as precursor ions and subjected to MS analysis. The collision energy was set at 20 eV and the fragmentor voltage was set at 175 V, using nitrogen as collision gas.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using non-targeted LC-MS n of ileal fluids from eleven ileostomates who completed a raspberry feeding study 3 , we identified novel compounds and putatively identified major components as fruit triterpenoid glycosides. The major triterpenoid had an apparent MW of 680 and could be purified from raspberry seeds.…”
mentioning
confidence: 99%